Case study: use of problem-based learning to develop students' technical and professional skills. (3rd March 2016) - Warnock, James N.; Mohammadi-Aragh, M. Jean
Abstract : Problem-based learning (PBL) is a pedagogy that has attracted attention for many biomedical engineering curricula. The aim of the current study was to address the research question, 'Does PBL enable students to develop desirable professional engineering skills?' The desirable skills identified were communication, teamwork, problem solving and self-directed learning. Forty-seven students enrolled in a biomedical materials course participated in the case study. Students worked in teams to complete a series of problems throughout the semester. The results showed that students made significant improvements in their problem-solving skills, written communication and self-directed learning. Students also demonstrated an ability to work in teams and communicate orally. In conclusion, this case study provides empirical evidence of the efficacy of PBL on student learning. We discuss findings from our study and provide observations of student performance and perceptions that could be useful for faculty and researchers interested in PBL for biomedical engineering education.